An Analysis of Language Styles Used by Gibran Rakabuming Raka in Political Interaction on Youtube Videos - Yuly Enjelina Br Pandia; Arsen Nahum Pasaribu; Donna Ria Pasaribu (Journal of Language Education (JoLE), 2025)
This study discusses the language style and aims to find out the types of language styles used by Gibran Rakabuming Raka in political interaction 5 YouTube videos. This study is based on the theory of Martin Joos (1967) where the writer applied the descriptive-qualitative method to get the data. The findings show that only four types were used by Gibran Rakabuming in political interactions in 5 YouTube videos, such as frozen style, formal style, consultative style, and casual style. The writer also found 51 data that were appropriate with the characteristics of language style in the 5 YouTube videos. There are 7 extracts of frozen style with 13,7%, 10 extracts of formal style with 19,6%, 27 extracts of consultative style with 53%, and 7 extracts of casual style with 13,7%. The findings reveal that the consultative style is the most dominant used than the other style because Gibran used the consultation sentences involved in sharing information and the mention of visions, missions, and programs resonating and it is tended about the characteristic of consultative style.